Effects and mechanisms of foliar application of silicon and selenium composite sols on diminishing cadmium and lead translocation and affiliated physiological and biochemical responses in hybrid rice (Oryza sativa L.) exposed to cadmium and lead. (July 2020) - Wang, Chengrun; Rong, Hong; Zhang, Xuebiao; Shi, Wenjun; Hong, Xiu; Liu, Weichen; Cao, Tong; Yu, Xianxian; Yu, Qifen
Abstract: Currently, exploring effective measures to reduce multiple toxic metals accumulation in rice grains is an urgent issue to be tackled. Pot experiments were thus conducted to explore the effects and mechanisms of foliar spraying with composite sols of silicon (Si) and selenium (Se) during tillering to booting stage on diminishing cadmium (Cd) and lead (Pb) translocation to rice grains and affiliated physiological and biochemical responses in rice seedlings grown in Cd + Pb-polluted soils (positive control). Results showed that Cd and Pb contents in leaves or grains were distinctly below the positive control by the sols. Compared to the positive control, transcriptions of Cd transporter-related genes including OsLCT1, OsCCX2, OsHMA2 and OsPCR1 genes in leaves, and OsLCT1, OsCCX2, TaCNR2 and OSPCR1 in peduncles were downregulated by the increasing sols. Meanwhile, Se-binding protein 1 was evidently upregulated, together to retard Cd and Pb translocation to rice grains. The sols not only upregulated transcriptions of Lhcb1, RbcL, and OsBTF3 genes and production of psbA, Lhcb1 and RbcL proteins, but also increased the chlorophylls contents and RuBP carboxylase activities in the leaves, improving photosynthesis. The sols restrained ROS production from NADPH oxidases, but activated glutathione peroxidase, alleviating oxidative stress and damage. Additionally, Se was significantly enriched and was existed as selenomethionine in the rice grains. However, Pb transporter-related genes remain to be specified. Thus, the composite sols have potential to reduce Cd and Pb accumulation, mitigate oxidative damage, and promote photosynthesis and organic Se enrichment in rice plants under Cd and Pb combined pollution. Highlights: Composite sols of Si and Se restrained ROS overproduction while activated GPx isozymes in rice plants exposed to Cd and Pb. The composite sols controlled Cd transporter-related genes, reducing Cd translocation to rice leaves and grains. Selenium-binding protein 1 was upregulated by the composite sols, retarding Cd and Pb transfer to rice grains. The composite sols upregulated photosynthesis-related genes, proteins and RuBP carboxylase in rice leaves.